Worked examples in electrical machines and drives - Hindmarsh, John, 1922- (Pergamon international library of science, technology, engineering, and social studies., 1982)
Worked Examples in Electrical Machines and Drives discusses methods in predicting and explaining electromechanical performance of several devices. The book is comprised of seven chapters that sequence the examples at increasing levels of difficulty. Chapter 1 provides an introduction and reviews the basic theories. The second chapter covers transformers, and the third chapter tackles d.c. machines. Chapter 4 is concerned with induction machines, while Chapter 5 deals with synchronous machines. Chapter 6 covers transient behavior, and Chapter 7 talks about power-electronic/electrical machine drives.